Facing chaos in parallel active filters using robust nonlinear control. - Guerrero Ramírez, Gerardo; Vela Valdés, Luis; Medina, Manuel Adam; Aguilar Justo, Marving; Astorga Zaragoza, Carlos (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Parallel active filters (PAF) are power electronic converters used to improve the electrical energy quality in distributed electrical systems. These filters are nonlinear systems due to the effect of the control signal. In addition, the variable nature of the electrical parameters makes them time-varying systems. PAF are used to obtain a good performance (harmonics generation of the load), however, chaos could be appear when some of their parameters change. Hence, the need of using a control law to face the existent parameter variation. In this paper a robust control law based on Lyapunov”™s redesign technique is used to design an additional control signal to face the parameter uncertainties and make that variation interval of parameters be greater without a chaos behavior. Simulations are presented to illustrate the performance of this controller.